Boosting the photocatalytic performance via defect-dependent interfacial interactions from electrostatic adsorption to chemical bridging. (15th December 2022) - Zhang, Youzi; Miao, Nanxi; Xin, Xu; Wang, Yijin; Zhu, Jinmeng; Guo, Peng; Wang, Junjie; Sobrido, Ana Jorge; Titirici, Maria-Magdalena; Li, Xuanhua
Abstract: The sluggish kinetics of interfacial electron transport and suboptimal photocatalytic stability are remaining challenges for designing efficient hetero-structured photocatalysts. Herein, we demonstrate a defect-induced interfacial interaction in the graphene oxide quantum dot/indium sulfide (GQD/In2 S3 ) hybrid, achieving remarkable stability and efficiency. By introducing sulfur vacancies into the In2 S3 structure, the interfacial electron exchange between the GQD and In2 S3 drastically increases, turning the interfacial interaction from weakly electrostatic adsorption to strongly chemical bridging. The interfacial interaction transition exhibits a great advantage in kinetics of interfacial electron transport with 12.32 times increase in the internal electric field intensity and less than half of carrier transport activation energy, while preventing the sulfur leaching in In2 S3 and enhancing the photocatalytic stability. Consequently, the GQD/In2 S3 with chemical bridging interface exhibits a dominant photocatalytic activity, with 40.9 mmol g −1 h −1, 22.7 folds higher than the analogous materials without S vacancies, and 96.1% H2 yield retention after 100 h tests. The deep understanding of the defect-induced interfacial modulation provides an insight for the design of high-performance hybrid photocatalyst. Graphical Abstract: We adjust the S vacancy content of In2 S3 to construct a In-O bond at interface of GQD/In2 S3 hybrid. The chemical bridging interface exhibits a great advantage in kinetics of interfacial electron transport and photocatalytic stability. The GQD/In2 S3 hybrid exhibits 22.7 folds enhance in photocatalytic H2 evolution activity, along with 96.1% H2 yield retention after 100 h tests. ga1 Highlights: GQD/In2 S3 with chemical bridging interface is prepared. Interfacial interaction of GQD/In2 S3 is turned via adjusting S vacancy content. Kinetics of interfacial electron transport and photocatalytic stability is enhanced.